(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This work provides a comprehensive overview of digital technology and its possible impact on the financial sector. Scientific papers and books have been used in the study of the topic to fully understand the topic provided. The paper also presents two drawings for the concept of the topic for the reader.